Recent insights into massive galaxy formation from observing structural evolution (Review). Issue Volume 15:Issue S359(2020) (March 2019) - Newman, Andrew B.
Abstract: New observations are probing the structures and kinematics of massive galaxies at a much greater level of detail than previously possible, especially during the first half of cosmic history. ALMA data now resolve the distribution of dust and molecular gas in massive galaxies to z ˜ 5. The stellar kinematics of several massive galaxies at z ˜ 2 – 3 have been spatially resolved using gravitational lensing, providing new information on the connection between quenching and morphological transformation. Star formation histories have been reconstructed for growing samples at z ˜ 0.8–2, revealing a wide range of timescales that correlate with galaxies' sizes and environments, providing evidence for multiple paths to quiescence. I review these and other developments and summarize the insights they have provided into massive galaxies' evolution.